A Literature Review on Tuberculosis Treatment Dosage, Side Effects, and PostTreatment Response: A Literature Review - Syahbaa', Zebaa; Yuniati, Shinta Karina (Journal of Diverse Medical Research: Medicosphere, 2025)
Background. Tuberculosis (TB) is an infectious disease that remains a global healthproblem. TB treatment requires lengthy drug regimens with varying doses and sideeffects, which can affect patient adherence to therapy.Objective. This review aims to provide a comprehensive overview of TB treatment,including dosage, side effects, and expected response after treatment.Methods. This study collected data from 21 journals downloaded from the Mendeleyplatform, covering studies that addressed common aspects of TB treatment.Results. TB treatment involves a combination of major drugs such as isoniazid,rifampicin, pyrazinamide, and ethambutol. Common side effects are gastrointestinaldisorders, hepatotoxicity, and neuropathy. Adherence to dosage and management of sideeffects are key to successful TB therapy.Conclusion. Proper dosing and monitoring of side effects are important factors inimproving patient adherence to TB treatment, which in turn can improve treatmentresponse.